The Knowledgement of Green Marketing and Consumer Decisions in Buying Organic Product with Fuzzy Analysis - Deliana, Yosini; Rum, Irlan Adiyatma (International Journal of Psychosocial Rehabilitation, 2020)
: In an effort of environment friendly, all elements related to the environment must be considered from producers to consumers. The problem is that even though people understand the importance of protecting the environment, behavior in protecting the environment and purchasing environmentally friendly products is still not appropriate. The purpose of this study is to analyze the clusters of consumers in the buying behavior of organic products, the knowledge matrix of green marketing, the prediction of consumers to buy organic products and what is most dominant factors of green marketing encourages consumers in purchasing organic products. The study was conducted from September to December 2019 in Bandung and , the sample was taken by random sampling of 205 respondents. Research finding, the prediction using Fuzzy Naive-Bayes (FNB) is a significant answer according to the theory proposed, namely that the higher the knowledge about green marketing, the higher the interest in buying green products. Research implication for further research, new variables allow for addition, and also the engineering of determining the degree of Fuzzy membership can be expanded. The originality of this research is to determine consumer decision with fuzzy, so the results will be closer to the natural characteristics of the respondents This research is useful for policy makers, market participants and stakeholders in educating consumers.